Uji Aktivitas Antioksidan Dari Kulit Buah Naga Merah (Hylocereus Polyrhizus) - Siti Puspitasari; Yulistia Budianti Soemarie; Aris Fadillah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Antioxidants are substances or compounds that have the ability to slow or delay, or even prevent, free radical reactions. Red dragon fruit skin has benefits as a source of antioxidants. This study aims to determine the antioxidant activity of ethanol extract, n-hexane fraction, ethyl acetate fraction and water fraction of red dragon fruit peel. The sample used in this research was the skin of red dragon fruit (Hylocereus polyrhizus) which was macerated with 70% ethanol and then fractionated using different solvents. Antioxidant activity testing was carried out using the DPPH method. The research results were shown by the IC50 value of the ethanol extract of 78.674 ± 19.618 µg/ml, the n-hexane fraction 129.942 ± 12.291 µg/ml, the ethyl acetate fraction 64.681 ± 19.820 µg/ml and the water fraction 73.038 ± 4.077 µg/ml. Based on the IC50 value obtained, the ethyl acetate fraction of red dragon fruit peel (Hylocereus polyrhizus) has the highest antioxidant activity.